Culicoides parauapebensis, a new species of the subgenus Hoffmania Fox from northern Brazil (Diptera: Ceratopogonidae) - Da Trindade, Rosimeire Lopes; Felippe-Bauer, Maria Luiza (Zootaxa, 2011)
Spinelli et al. (1993) in their revision of the Neotropical species of the guttatus species group of the subgenus Culicoides (Hoffmania) Fox, included 30 species of which 17 inhabit the Amazonian Region. Subsequently, Ronderos and Spinelli (1995) described C. ferreyrai from Argentina and Spinelli and Borkent (2004) C. annettae from Costa Rica. During entomological surveys in the municipalities of Parauapebas and São Geraldo do Araguaia, Pará, Brazil, the collected specimens of Culicoides included an undescribed species belonging to the guttatus species group. In this paper we describe and illustrate it, arising to 33 the number of the Neotropical species of this group.